Association of Autoimmune Hepatitis and Celiac Disease: Role of Gluten-Free Diet in Reversing Liver Dysfunction - Iqbal, Umair (J Investig Med High Impact Case Rep, 2017)
Autoimmune hepatitis (AIH) is a chronic inflammation of liver with unclear etiology. It is frequently associated other autoimmune diseases, and its association with celiac disease (CD) is well established. In this article, we describe the case of a 50-year-old male with long-standing AIH taking azathioprine for 10 years, evaluated for flares in transaminases. Despite adding high-dose corticosteroids, his transaminases and bilirubin remained high. Serology for CD was ordered, which revealed elevated tissue transglutaminase antibody IgG and endomysial IgA, which was further confirmed by endoscopic biopsy. Strict gluten-free diet was advised and now for over 2 years he is in remission with azathioprine and budesonide. This emphasizes the role of gluten-free diet in reversing liver dysfunction in patients with AIH, and clinicians should consider screening for CD in patients with AIH with persistent elevation of liver enzymes despite immunosuppressant treatment.